Halo Nevi in children: A separate entity or a sign of vitiligo? - N A Bishurul Hafi; Romita Bachaspatimayum; Ronibala Soraisham; N CP Muhammed (Wolters Kluwer Medknow Publications, 2019)
Background: Halo nevi (HN) can present either singly or along with vitiligo. Whether they are different entities, remains debatable. Objectives: The objective of the study is to compare clinicoepidemiologic and laboratory factors associated with HN, HN with vitiligo and vitiligo alone, in children. Methodology: A total of 205 children <18 years who presented to the outpatient department were sampled purposively to three groups: (a) HN without vitiligo, (b) HN with vitiligo, and (c) Vitiligo without HN. Results: There were seven patients in Group A, 11 in Group B, and 187 in Group C. A statistically significant difference was noted between Group B and C in the age of onset (0.004) as well as the age of presentation (0.031). Even though the disease process had started in head-and-neck region in more than half of the patients in each group, HN was present mostly on trunk (90.9%) in Group B and in 28.6% in Group A. No statistically significant difference was noted in associated disorders, personal or family history of autoimmune disorders, koebnerization, leukotrichia, or laboratory tests. Conclusions: Our study, particularly done among pediatric population, has failed to demonstrate much significant differences between HN and vitiligo, except in the age of presentation as well as the age of onset. It further gives proof to substantiate the hypothesis that HN can be a part of clinical spectra of vitiligo.